Competing Knowledges - Wissen Im Widerstreit. - Horatschek, Anna-Margaretha. (Abhandlungen der Akademie der Wissenschaften in Hamburg Series, 2020)
At irregular intervals, the Abhandlungen der Akademie der Wissenschaften in Hamburg [Proceedings of the Academy of Sciences in Hamburg] will publish monographs or conference reports from subfields of the natural sciences, humanities, and social sciences researched at this interdisciplinary academy. These manuscripts will be selected based upon their contribution to solving fundamental research problems, to exploring contemporary and historical issues, or to reporting about scientific discoveries of social significance.